2021
DOI: 10.1016/j.bbih.2021.100283
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocyte and monocyte subsets are dysregulated in type 1 diabetes patients with peripheral neuropathic pain

Abstract: Diabetic neuropathic pain is a common and devastating complication of type 1 diabetes, but the mechanism by which it develops and persists is yet to be fully elucidated. This study utilised high-dimensional suspension mass cytometry in a pilot cohort to investigate differences in peripheral blood immunophenotypes between type 1 diabetes patients with (n ​= ​9) and without (n ​= ​9) peripheral neuropathic pain. The abundance and activation of several leukocyte subsets were investigated with unsupervised cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“… 4 , 11 This is true for other chronic pain conditions as well, with the largest focus overall on macrophages/monocytes, T cells, and mast cells. 39 , 43 , 56 Technological limitations are perhaps an important reason for this cell type–focused approach. Although multicolor fluorescence-based flow cytometry was introduced approximately 4 decades ago and has proven to be an extremely effective tool for the phenotypic characterization and functional analysis of immune cells, it still cannot capture all immune cells subtypes in one run.…”
Section: Unbiased Immune Profiling Of Pain Phenotypesmentioning
confidence: 99%
“… 4 , 11 This is true for other chronic pain conditions as well, with the largest focus overall on macrophages/monocytes, T cells, and mast cells. 39 , 43 , 56 Technological limitations are perhaps an important reason for this cell type–focused approach. Although multicolor fluorescence-based flow cytometry was introduced approximately 4 decades ago and has proven to be an extremely effective tool for the phenotypic characterization and functional analysis of immune cells, it still cannot capture all immune cells subtypes in one run.…”
Section: Unbiased Immune Profiling Of Pain Phenotypesmentioning
confidence: 99%
“…Th1‐ and Th17‐type responses have been associated with enhanced pain, while T helper 2 cell and regulatory T‐cell responses have been associated with a reduction in pain 5–7 . Clinical studies, several using high‐dimensional mass cytometry, have shown increased activation of Th1 and regulatory T‐cell subsets, and reduced numbers of Th17 in blood from chronic neuropathic pain cohorts 8–11 . Despite this, the T‐cell receptor repertoire of T‐cell subsets in patients with chronic pain have not yet been evaluated.…”
Section: Figurementioning
confidence: 99%
“…Thus, during normal injury repair, S. aureus augments endogenous neuroimmune interactions to re-establish homeostasis. (b) In patients with chronic neuropathic pain, altered numbers of circulating T cells, for example, decreased Th17 and increased Th1 cells and Tregs, [8][9][10][11] may be indictive of an altered balance of T-cell populations in the skin. This, in combination with reduced intraepidermal nerve fiber density (IENFD) and a potential reduction in IL-17RA expression, may interfere with Th17-mediated neuronal repair and, therefore, contribute to continued nociceptive signaling and chronic pain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,67,140 There are also multiple studies investigating myeloid cell involvement in human chronic pain states. Circulating myeloid cells and mediators in blood, serum, and blister fluid have been increasingly well characterised, eg, changes in monocyte frequency and activation state in diabetic neuropathic pain and complex regional pain syndrome 1,4,98,111,127,145 ; increased TNF, IL-6, and neuropeptides in fibromyalgia 153 ; and increased macrophage reactivity in endometriotic serum, peritoneum, and endometrium in endometriosis-associated pain. 36 Human tissue investigations have largely been performed in the skin, given the relative accessibility, highly characterised cellular environment, and the appreciation of a critical role of epidermal and dermal nerve fibres in neuropathic pain (see Ref.…”
Section: Introductionmentioning
confidence: 99%